2018
DOI: 10.1155/2018/2893012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Intestinal Infectious Diseases due to Protozoa and Bacteria in Mexico: Analysis of National Surveillance Records from 2003 to 2012

Abstract: Background According to national epidemiological surveillance records, in Mexico six intestinal infectious diseases (IID) are among the top infectious communicable diseases. However, their incidence, relative importance, and spatial patterns have not been studied in detail. Aims We examine the epidemiology of IID due to bacteria and protozoa to identify which diseases are most important at two spatial scales, what is their integrated importance locally, and how their incidence correlates with Human Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
(30 reference statements)
1
10
2
Order By: Relevance
“…Although the Mexican government has little information about the incidence of norovirus in the country [ 28 ], in this study, norovirus was found at a high percentage in hospitalized patients and, in some cases, co-infecting with bacteria (or parasite). Since these conditions could worsen the clinical stage of patients, it is urgent to implement routine methods to detect this virus in food and people to reduce viral dispersion and prevalence in the population with special attention in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Although the Mexican government has little information about the incidence of norovirus in the country [ 28 ], in this study, norovirus was found at a high percentage in hospitalized patients and, in some cases, co-infecting with bacteria (or parasite). Since these conditions could worsen the clinical stage of patients, it is urgent to implement routine methods to detect this virus in food and people to reduce viral dispersion and prevalence in the population with special attention in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 85%
“…Similar data were reported in France, where from 17,281 hospitalized patients suffering foodborne illness, 59% of cases were caused by bacteria, 38% by virus, and 3% by parasites; the pathogens more often found included Campylobacter, Salmonella, and norovirus, accounting for 76% of cases [ 27 ]. In Mexico, various pathogens are commonly reported as cause of diarrhea: Salmonella , Shigella , Escherichia , Vibrio , Campylobacter , Yersinia, C. difficile, Aeromonas , and several amoebas and viruses, such as norovirus [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal protozoan infections were documented among both immunosuppressed and immunocompetent patients (Fletcher et al, 2012;Han and Weiss, 2017). Cryptosporidium, Entamoeba and microsporidia are considered as major intestinal Protozoa of public health importance (Kosek et al, 2001 ;Haque et al, 2003;Han and Weiss, 2017;Daniel et al, 2018;Kimosop et al, 2019;Ögren et al, 2020) due to being responsible for waterborne diseases in human.…”
Section: Microsporidiamentioning
confidence: 99%